Role of Notary in Change of Name of Limited Liability Company - Detkri Badhiron; Umar Ma'ruf; Ngadino Ngadino (Sultan Agung Notary Law Review, 2021)
This research aims at untuk know and analyze the factors that cause PT. Mega Transformation Indonesia changed to PT. Djaja Bangun Rahardja, besides that this research is also to determine and analyze the role of the Notary in the change of PT. Mega Transformation Indonesia to become PT. Djaja Bangun Rahardja associated with Act No. 40 of 2007 concerning Limited Liability Companies and the latter to identify and analyze the process of barriers and solutions in the process of changing PT. Mega Transformation Indonesia to become PT. Djaja Bangun Rahardja associated with Act No. 40 of 2007 concerning Limited Liability Companies.The approach method in this research isjuridical empirical. Juridical approach (law is seen as norms or das sollen), because in discussing the problem of this research using legal materials (both written and unwritten law or both primary and secondary legal materials). An empirical approach (law as a social, cultural or das sein reality), because in this study primary data obtained from the field were used. So, the empirical juridical approach in this study means that in analyzing the problem it is done by combining legal materials (which are secondary data) with primary data obtained in the field, namely about how the role of the Notary requires empirical research on Notaries who process name changes. names of shareholders and changes in the Board of Directors. The specifications used in this research are descriptive-analytic, which is intended to provide as accurate a data as possible about a condition or other symptoms, because this research is expected to provide a detailed, systematic and comprehensive description of the role of the notary in processing the name change of a limited liability company. The data required includes dataPrimary data is data obtained from the field, data is obtained from respondents. Respondent is a person or community who provides answers to questions from researchers. Secondary data, namely data obtained from or derived from library materials, secondary data collected in this study include primary legal materials, secondary legal materials and tertiary legal materials.. In discussing the subject matter and analyzing the data that has been obtained, the authors use all the information and data that has been obtained, both primary and secondary data. Then the authors analyzed qualitatively which was then presented descriptively.